Comparison of Prediction Programs for Short Wave Circuit Link from Iraq to Test points on Both Earth Hemispheres during Solar Minimum - Hasan, Ahmed Kadhim (Al-Khwarizmi Engineering Journal, 2021)
This paper compare  the accurecy of HF propagation  prediction programs for  HF circuits links between Iraq and  different points world wide  during August 2018 when  solar cycle 24 (start 2009 end 2020) is at minimun activity and also find out the best communication mode  used. The prediction   programs like Voice of America Coverage Analysis Program (VOACAP) and ITU Recommendation RS 533 (REC533 )  had been used to generat HF circuit link  parameters like Maximum Usable Frequency ( MUF) and Frequency of Transsmision (FOT) .Depending  on the predicted parameters (data)  , real radio contacts had been done using a radio transceiver from Icom  model IC 7100 with 100W RF power, tuner box and homemade  dipole antenna of 10 m length and  8m height above ground. From  correlation between the predicted data and observed data  the result was not accurate .